SUPLEMENTASI BEKATUL BERAS HITAM UNTUK MENGHAMBAT PERKEMBANGAN KANKER KOLON MELALUI PENGHAMBATAN PROLIFERASI DAN PENINGKATAN APOPTOSIS PADA MENCIT BALB/C - Yeni Kurniati; Slamet Budijanto; Lilis Nuraida; Fitriya Nur Annisa Dewi; Safrida, Safrida (Media Bina Ilmiah, 2024)
Colon cancer is one of the degenerative diseases caused of death after lung and breast cancer. One of the food ingredients that potentially inhibites the occurrence of colon cancer is black rice bran. The aim of this study was to found the effect of black rice bran on apoptosis and cell proliferation on BALB/c mice. In this study, BALB/c mice were divided into three groups, they are normal group (K-), AOM/DSS induced tumor group (K+), and feeding black rice bran with induction of AOM/DSS (BRB). At the end of the study, all mice were terminated and the presence of nodule were analysed in colon tissue used imageJ application. The expression of caspase-3, caspase-8, and PCNA were analysed in colon tissue used q-RT PCR. The data obtained by analyzes of variance (ANOVA) and continued by Tukey HD different test at 5% level. Administration of BRB significantly decreased the expression of PCNA in comparison with that of control mice (K+) (0.58 ± 0.09 vs 5.22 ± 0.80). The expression of caspase 3 (0.91 ± 0.20) and caspase 8 (0.36 ± 0.15) of BRB significantly increased comparasion with control mice K+. Our results thus indicated that black rice bran performed to suppresed proliferation and induced apoptosis